KOMUNIKASI ANTARBUDAYA PARA SURFER DI LOKASI PARIWISATA PANTAI BATUKARAS - Hana Silvana (Fakultas Seni Rupa dan Desain ITB, 2010)
This research attempts to describe an intercultural communication in Batukaras Beach, Subdistrict of Cijulang, Regency of Ciamis. Tourism specification that is well known in Batukaras is surfing. This fact allows youth groups as one element of fisherman society to work seriously at surfing. Meetings between two or more cultures in Batukaras are focused on the surfers, which are devided into local surfers and foreign surfers. The method used in this study is an ethnographic method with a qualitative approach. To explore the data, participant observation, interviews, and literature study are used in this research. The results of observation on surfers and implementation of tourism in Batukaras give significant descriptions in finding patterns of local surfer behavior and the implementation forms of tourism of surfing that is carried out in Batukaras. The truth and relevance of the observation results are later confirmed with informations obtained through unstructured in-depth interviews of informants. According to the research result, it shows that in the late 1990s Batukaras as a tourist destination especially surfing tourism provides an opportunity for intercultural meeting in Batukaras. The intercultural meeting produces a cultural mixing (diffusion) that leads to a new cultural formation of young local people. The distinctive cultures of young people of fisherman family member of Batukaras are recognized and acknowledged by the dominant society, which is fishermen. The acknowledgement gives strength to the young to act in a context of distinctive culture that is carried by young people. However, The most crucial finding from the acknowledgement of these young people identity is the occurrence of culture denomination symptoms within the fisherman communities in Batukaras.